2021
DOI: 10.3390/ijms221910182
|View full text |Cite
|
Sign up to set email alerts
|

Good Cholesterol Gone Bad? HDL and COVID-19

Abstract: The transmissible respiratory disease COVID-19, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has affected millions of people worldwide since its first reported outbreak in December of 2019 in Wuhan, China. Since then, multiple studies have shown an inverse correlation between the levels of high-density lipoprotein (HDL) particles and the severity of COVID-19, with low HDL levels being associated with an increased risk of severe outcomes. Some studies revealed that HDL binds to SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 208 publications
(316 reference statements)
0
24
0
Order By: Relevance
“…Glycated HDL were a smaller particle size and presented a loss of PON activity to display the atherogenic properties. The pro-inflammatory effects of modified HDL with a loss of PON activity were mediated by cellular signaling between the blocking of scavenger receptor-B-I (SR-B-I) and the binding of glycated HDL [ 71 ].…”
Section: Hdl Qualitymentioning
confidence: 99%
“…Glycated HDL were a smaller particle size and presented a loss of PON activity to display the atherogenic properties. The pro-inflammatory effects of modified HDL with a loss of PON activity were mediated by cellular signaling between the blocking of scavenger receptor-B-I (SR-B-I) and the binding of glycated HDL [ 71 ].…”
Section: Hdl Qualitymentioning
confidence: 99%
“…In addition, decreased number of small HDL particles is inversely associated with the disease activity score and CRP levels during inflammatory states [ 27 ]. Studies during COVID-19 pandemic showed reduced HDL-C levels reflecting reduced levels of HDL particles in plasma of severe COVID-19 patients [ 28 , 29 ]. We demonstrated low HDL-C levels are related to severity of COVID-19 in accordance with the recent literature.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis and utilization of cholesterol is a strongly controlled method that prevents its overdeposition of tissue. However, abnormal synthesis and utilization of cholesterol due to certain inherited diseases, infection, and/or unhealthy lifestyle, contributes to the development of hyperlipidemia and hypolipidemia [246][247][248][249][250]. Several illnesses, such as atherosclerosis, xanthomas, tangier, strokes, and cardiovascular diseases have been linked to high cholesterol levels [251][252][253][254].…”
Section: Cholesterol-induced α-Syn Abnormalities In Pdmentioning
confidence: 99%